Statistics e-learning platforms evaluation: Case study - Taleb Ahmad; Wolfgang Karl Härdle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
With the increase of e-learning by universities and educational institutes in the world through more electronic platforms, come the questions to researchers, educators and designers of electronic platforms about feasibility and using this method of learning. Are we achieving the desired goals and improving the quality of education? Are we improving their performance and ability to self-study without the need for a teacher? Is e-learning an effective and successful method from the students views? In this paper, we consider evaluate e-learning systems in statistics. We make an evaluation study, we analyze a students sample of the methods: Factor analysis, Logit model. The common aim of this evaluation is to provide data to justify the results or evidence to support that the e-learning platforms are helping the students to learn more effectively. The questionnaire covers information about e-learning evaluation criterias. Some of these criterias are: Navigability, applicability, instructional structure and interactivity.
Keywords: I21; C19; 330; E-learning; evaluation; statistical software; Statistische Methodenlehre; Computergestütztes Lernen; Internet; Wirtschaftsstudium; Wirtschaftspädagogik; Bewertung